2008
DOI: 10.1063/1.2887906
|View full text |Cite
|
Sign up to set email alerts
|

Impact of annealing on morphology and ferromagnetism of ZnO nanorods

Abstract: Room temperature ferromagnetism has been observed in ZnO nanorods prepared by hydrothermal method. Saturation magnetization of ϳ0.004 emu/ g was measured in the nanorods with diameters of ϳ10 nm and lengths of below 100 nm, and the magnetization reduced with the increase of the size. Annealing of the samples at 900°C in air completely transformed the nanorods into twinning structures and weakened the magnetizations. The mechanism of morphology transformation was discussed. Analysis indicates that the interstit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 22 publications
5
53
1
Order By: Relevance
“…Because the sample contains multiple compositions, we cannot accurately determine the magnetism in terms of formula unit. Nevertheless, the observed value of saturation magnetization in A-AZO is comparable to what reported for nanograined ZnO films (0.05 emu/g), 12 but much higher than those of undoped ZnO nanoparticles obtained via chemical routes (between 0.0015 and 0.0022 emu/g) 40,41 and ZnO nanorods (0.004 emu/g), 42 as well as the thiol-capped ZnO nanoparticles (0.003 emu/g). 20 To find out the origin of magnetism in the annealed ZnO/Al 2 O 3 core-shell NWs, we measured a control sample of ZnAl 2 O 4 nanocrystals, which were fabricated using the conventional solid stat reaction route from high-purity ZnO and Al 2 O 3 powders, and found that ZnAl 2 O 4 nanocrystals exhibits only a diamagnetic behavior [ Fig.…”
supporting
confidence: 59%
“…Because the sample contains multiple compositions, we cannot accurately determine the magnetism in terms of formula unit. Nevertheless, the observed value of saturation magnetization in A-AZO is comparable to what reported for nanograined ZnO films (0.05 emu/g), 12 but much higher than those of undoped ZnO nanoparticles obtained via chemical routes (between 0.0015 and 0.0022 emu/g) 40,41 and ZnO nanorods (0.004 emu/g), 42 as well as the thiol-capped ZnO nanoparticles (0.003 emu/g). 20 To find out the origin of magnetism in the annealed ZnO/Al 2 O 3 core-shell NWs, we measured a control sample of ZnAl 2 O 4 nanocrystals, which were fabricated using the conventional solid stat reaction route from high-purity ZnO and Al 2 O 3 powders, and found that ZnAl 2 O 4 nanocrystals exhibits only a diamagnetic behavior [ Fig.…”
supporting
confidence: 59%
“…The UV emission is well understood as a near-band edge ͑NBE͒ exciton emission arising from the recombination of photogenerated charge carriers across the band gap of ZnO, while a variety of deep-level defects have been proposed as possible contributors to the emission in the visible regime. Recent reports have attributed the green light emission centered at 494 nm ͑2.51 eV͒ to an oxygen vacancy ͑V O ͒, 36 the emission feature at 520 nm ͑2.38 eV͒ to antisite oxide ͑O Zn ͒, 37 whereas the yellow to red emission contributions from 540 to 700 nm are attributed to oxygen interstitials ͑O i ͒. 38 It is generally believed that the UV emission intensity at RT is related to a variation in electron concentration, 39 while the visible emission intensity correlates directly with intrinsic defect densities in the material.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The blue emission peak observed at around 442 nm (2.80 eV) is probably due to the defect levels such as metal defects and or oxygen vacancies [40]. However, green emission peaks appeared at 481 nm (2.57 eV) and 496 nm (2.50 eV) in the visible range is due to the intrinsic defects and oxygen vacancy [41]. Moreover, the presence of green emission at around 529 nm (2.34 eV), which confirm the recombination of a photo generated hole and metal defects.…”
Section: Photoluminescence (Pl) Studiesmentioning
confidence: 84%